Play with social media ‘Instagram’ in EFL Writing and Critical Thinking Skill: how can? - Ni Ketut Ayu Sandya Dewi (STKIP AGAMA HINDU SINGARAJA, 2022)
This paper aims at explaining how social media Instagram can be implemented in EFL writing competence and critical thinking skill. This paper is library research. The data were collected by analyzing the data information. There are several trending social media applications such as Facebook, Twitter, YouTube, WhatsApp, Line, and Google+, however the most popular application used is Instagram. It provides features that can make both teacher and students enjoying the learning process. Besides, it enables students to avoid their stress and boredom. Rather than that, Instagram can be used to support the four language skills. However, some studies found that Instagram is used for developing writing skill. Additionally, by commenting the uploading photos and videos on Instagram, it can help students in increasing their opinions, ideas, and critical thinking skill.